2016
DOI: 10.1371/journal.pone.0162403
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Rubella Virus Strains Detected in Spain, 1998-2014

Abstract: The National Plan for the Elimination of Rubella was implemented in Spain in 2008 using the logistics of the National Plan for the Elimination of Measles that have been employed since year 2000. Molecular characterization of rubella virus (RUBV) is important for disease surveillance and for monitoring elimination of the disease throughout the world. We describe the first complete series of data regarding the circulation of RUBV genotypes in Spain. The 739-nucleotide fragment designated by the WHO for RUBV geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Rubella virus is formed by the structural polypeptides, the membrane glycoproteins E1 and E2 and a single nonglycosylated RNA-associated capsid protein C (Lee & Bowden, 2000). In a recent research, five genotypes of RV, 1E, 2B, 1J, 1I, and 1a were identified (Martí nez-Torres et al, 2016). The vaccine is a live attenuated preparation of the virus (RA 27/3), which induces immunity by producing a modified rubella infection (Parkman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Rubella virus is formed by the structural polypeptides, the membrane glycoproteins E1 and E2 and a single nonglycosylated RNA-associated capsid protein C (Lee & Bowden, 2000). In a recent research, five genotypes of RV, 1E, 2B, 1J, 1I, and 1a were identified (Martí nez-Torres et al, 2016). The vaccine is a live attenuated preparation of the virus (RA 27/3), which induces immunity by producing a modified rubella infection (Parkman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, a second dose at 11 years was introduced. After 1999, this second dose was given to 4-year-old children, and so it is still in the current immunization schedule [ 6 ]. The high response rate to a single dose of rubella vaccine (≥95%) and the long-term persistence of protection in vaccines do not support a routine requirement for a second dose of rubella vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, strains belonging to only two genotypes (1E and 2B) were reported to the global Rubella Nucleotide Surveillance (RubeNS) database (www.who-rubella.org/files/wer8832.pdf), [58]. In many countries, genotype replacements were noted (e.g., [59][60][61]) and lately involve, most often, genotype 2B as the new dominant genotype. While the reasons for the observed dominance are unknown, the question has been raised whether 2B strains have higher transmission ability [62].…”
Section: Implications Of Genetic Variations Of Teratogenic Virusesmentioning
confidence: 99%